ORTHOEPIC EXERCISE - THE BASIS OF DEVELOPING SKILLS - Samandarova Gulkhayo Abdukarim kizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article expands the scope of orthoepy and the oral point, and introduces some techniques for developing students’ speech, teaching them to think, working on sound, and developing orthoepic skills in writing lessons.